Tinjauan Kaidah Fikih Wakaf Uang Berasal Dari Asnaf Fisabilillah; Sinergi Wakaf Produktif Dan Zakat: Sinergi Wakaf Produktif Dan Zakat - Ishandawi, Ishandawi; Januri , Fauzan; Muharni , Yusraini (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
This paper examines the fiqh (Islamic jurisprudence) principles related to the permissibility of waqfing (endowing) zakat money for fisabilillah (in the way of Allah), as well as an effort to synergize productive waqf and zakat. A qualitative analysis shows that the fiqh principles can support the use of zakat funds for fisabilillah as waqf money for the benefit of the ummah (Muslim community). Productive waqf from zakat fisabilillah has the potential to bring long-term benefits to the ummah. Based on the fiqh principles that allow it, it strengthens the ummah's conviction to implement productive waqf from zakat fisabilillah.